The Role of Bali's Traditional Subak Farming System in the Preservation of Natural and Cultural Resources - Putu Doddy Heka Ardana; Dewa Oka Suparwata; Arief Sudrajat; Sri Chatun; Iwan Harsono (West Science Nature and Technology, 2024)
The Subak traditional farming system in Bali embodies a harmonious relationship between humans, nature, and spirituality, epitomizing the Balinese philosophy of "Tri Hita Karana." This qualitative study explores the role of the Subak system in the preservation of natural and cultural resources in Bali. Through interviews with Subak farmers, water temple priests, and other stakeholders, as well as participant observation and document analysis, the study examines the ecological functions, cultural significance, and challenges facing the Subak system. The findings reveal that the Subak system plays a vital role in maintaining ecological balance, biodiversity, and soil health in Bali's landscapes. Furthermore, the Subak system holds profound cultural significance, serving as a spiritual anchor, fostering community cohesion, and preserving cultural heritage. However, the Subak system faces numerous challenges, including urbanization, water scarcity, and demographic shifts, which threaten its sustainability and resilience. Addressing these challenges requires concerted efforts to protect Subak landscapes, promote traditional farming practices, and empower local communities. By recognizing the holistic value of the Subak system, stakeholders can work together to ensure the preservation of Bali's natural and cultural heritage for future generations.